2021
DOI: 10.1007/s00392-021-01814-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined renal and common hepatic artery denervation as a novel approach to reduce cardiometabolic risk: technical approach, feasibility and safety in a pre-clinical model

Abstract: Background Cardiovascular and metabolic regulation is governed by neurohumoral signalling in relevant organs such as kidney, liver, pancreas, duodenum, adipose tissue, and skeletal muscle. Combined targeting of relevant neural outflows may provide a unique therapeutic opportunity for cardiometabolic disease. Objectives We aimed to investigate the feasibility, safety, and performance of a novel device-based approach for multi-organ denervation in a swine mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
1
5
0
1
Order By: Relevance
“…In this context, continuous monitorisation of MAP is essential to reveal the immediate, acute, and long-term effects of non-invasive abdominal electrical stimulation. Combined denervation of the hepatic and renal arteries has also been investigated in the literature and demonstrated to be capable of reducing cardiometabolic risk [22]. The present study also demonstrated the effect of abdominal con guration on both the hepatic and renal artery modulation which may have an impact on cardiometabolic risk.…”
Section: Renal Arterysupporting
confidence: 64%
“…In this context, continuous monitorisation of MAP is essential to reveal the immediate, acute, and long-term effects of non-invasive abdominal electrical stimulation. Combined denervation of the hepatic and renal arteries has also been investigated in the literature and demonstrated to be capable of reducing cardiometabolic risk [22]. The present study also demonstrated the effect of abdominal con guration on both the hepatic and renal artery modulation which may have an impact on cardiometabolic risk.…”
Section: Renal Arterysupporting
confidence: 64%
“…In addition, the Metavention has developed an integrated catheter ablation system, the iRF Denervation System (Metavention, Maple Grove, MN, USA), which allows for combined denervation of the hepatic and renal arteries. A significant decrease in norepinephrine concentrations in liver and kidney tissues at 90 days after the procedure compared with baseline (all p < 0.05), suggesting the possible effectiveness of combined ablation ( 142 ). Clinical studies on the iRF system were also conducted in 2020, and the DeLIVER study (NCT04285554) aimed to explore the safety of the iRF system and its effects on metabolic markers such as blood glucose and lipids, and its results are expected.…”
Section: Hepatic Artery Denervationmentioning
confidence: 95%
“…Kraft et al 59 established that surgical sympathetic denervation of the common hepatic artery in a canine model decreased both the hepatic and β‐cell defects caused by a high‐fat, high‐fructose diet, thereby increasing glucose tolerance. Kiuchi et al 61 investigated the feasibility, safety, and efficacy of EDN of both hepatic and renal arteries in a swine model, achieving significant and sustained denervation without major safety events. Tzafriri et al 62 analyzed the nerves and adjacent anatomies surrounding the human common hepatic artery to guide the clinical translation of catheter‐based denervation.…”
Section: Endovascular Denervationmentioning
confidence: 99%